Penguatan Kompetensi Canva AI dan Literasi Keuangan melalui Platform e-Learning VocaSmart bagi Siswa SMK YAPINKTEK Tangerang - Agus Mulyanto; Yuni Roza; Nasril Sany; Esa Firmansyah Muchlis; Widi Pramudiya; Firmansyah Apriadhi; Atikah Rifdah Ansyari; Jenny Agustina Rahman (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program aims to improve Canva AI design competencies and financial literacy among students of SMK YAPINKTEK Tangerang through the VocaSmart e-learning platform. This workshop-based program involved 40 participants consisting of 35 students and 5 teachers. Evaluation was conducted through pre-tests, post-tests, practical assessments, and satisfaction questionnaires. The results showed an increase in the average Canva AI score from 62.4 to 80.6 and financial literacy from 58.9 to 74.6. The participant satisfaction rate reached 84.3%, while 87.6% of participants responded positively to the VocaSmart platform. These findings indicate that integrated digital training is effective in improving vocational competencies and has the potential to be implemented in similar schools.